Deity - Steven Dunne (London Headline, 2012)
When four Derby College students are reported missing, few in Derby CID, least of all DI Damen Brook, pay much attention. But then a film on the internet is discovered purporting to show the students committing mass suicide. If it's real, why did they kill themselves when they had such bright futures ahead of them.
Keywords: Brook, Damen (Fictitious character) -- Fiction